(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The purpose of the present study was to compare the marginal integrity of resin modified glass ionomer cement with that of resin sealant, in vitro. Forty artificial pit and fissure cavities were prepared in occlusal surface of extracted premolar teeth by using ¼ round carbide bur. Cavities were condensed with artificial organic debris followed by cleaning with prophylaxis pumice brush and paste and then separated into two treatment groups. In Group A, 15 fissure cavities were sealed by resin sealant and in Group B, 15 fissure cavities were sealed by resin modified glass ionomer sealant. These specimens were subjected to thermo-cycling followed by dye penetration test. The remaining 5 cavities from each group were analyzed for debris score by the SEM. The results of the microleakage test showed that the efficacy of preventing microleakage of samples sealed by resin modified glass ionomer sealant was higher than the samples sealed by resin sealant. However, no significant differences were found. It can be concluded that use of resin modified glass ionomer sealant is a good alternative for sealing pits and fissures.